Epicardial adipose tissue thickness is associated with reduced peak oxygen consumption and systolic reserve in patients with type 2 diabetes and normal heart function. Issue 1 (27th September 2022) - Nesti, Lorenzo; Pugliese, Nicola Riccardo; Chiriacò, Martina; Trico, Domenico; Baldi, Simona; Natali, Andrea
Abstract: Aim: To investigate the impact of epicardial adipose tissue (EAT) thickness on cardiopulmonary performance in patients with type 2 diabetes (T2D) and normal heart function. Materials and methods: We analysed EAT thickness in subjects with T2D and normal biventricular systo‐diastolic functions undergoing a maximal cardiopulmonary exercise test combined with stress echocardiography, speckle tracking and pulmonary function assessment, as well as serum N‐terminal pro B‐type natriuretic peptide (NT‐proBNP). Results: In the 72 subjects enrolled, those with EAT thickness above the median (> 5 mm) showed higher body fat mass, smaller indexed left ventricular dimensions and marginally reduced diastolic function variables at rest. Higher EAT thickness was associated with lower peak oxygen uptake (VO2peak 17.1 ± 3.6 vs. 21.0 ± 5.7 ml/min/kg, P = .001), reduced systolic reserve (ΔS′ 4.6 ± 1.6 vs. 5.8 ± 2.5 m/s, P = .02) and higher natriuretic peptides (NT‐proBNP 64 [29‐165] vs. 31 [26‐139] pg/ml, P = .04), as well as chronotropic insufficiency and impaired heart rate recovery. Ventilatory variables and peripheral oxygen extraction were not different between groups. EAT was independently associated with VO2peak and linearly and negatively correlated with peak heart rate, heart rate recovery, workload, VO2 at the anaerobic threshold and at peak, and cardiac power output, and was directly correlated with natriuretic peptides. Conclusion: Higher EAT thickness in T2D is associated with worse cardiopulmonary performance and multiple traits of subclinical cardiac systolic dysfunction.